Looking Back, Looking Ahead: WCC Engagement in Interreligious Dialogue - Pratt, Douglas (The ecumenical review, 2021)
Apart from presenting a report and recommendations on Christian–Jewish relations in the aftermath of the Second World War, the 1st Assembly of the World Council of Churches (WCC), in 1948, did not address interreligious engagement. Nevertheless, within a decade the WCC had begun engagement with peoples of other faiths, spearheaded by a dialogue sub-unit and a study programme on interreligious dialogue that ran to 1971. This article sketches some of the main developmental moments of the WCC’s engagement in interreligious dialogue through the second half of the 20th century and into the first two decades of the 21st. It identifies three dialogue models employed by the WCC and suggests an outline of a theology of dialogue – theology for, in, and after dialogue – and closes with a comment on the future of dialogue. WCC engagement in interreligious dialogue is as exciting, necessary, and hopeful as it ever was.